Implication of groundwater fluctuation on the seasonal salt dynamic in the Harran Plain, south-eastern Turkey - Cullu, M.A.; Aydemir, M.; Qadir, Manzoor; Almaca, A.; Ozturkmen, A.R.; Bilgic, A.; Agca, N. (Wiley, 2010)
Inefficient farm-level water management aggravates groundwater fluctuation and salt accumulation particularly in arid and semi-arid irrigated agriculture. Inappropriate water management practices in the Harran Plain are a good example. A study was carried out to investigate the effect of groundwater fluctuation on the seasonal salt dynamic in four widespread soil series in the Harran Plain with different natural drainage, south-eastern Turkey. Four profiles were excavated and soil samples were collected seasonally up to 100 cm depth with 10 cm intervals. Similarly, irrigation and groundwater samples were collected from the fields where soil sampling was carried out. Significant seasonal variations in the salt dynamic were observed with the fluctuation levels of the groundwater. Total salt content at 1 m soil depth remained constant during the year, however salt fluctuation throughout the root zone in the growing season exceeded the threshold values of corn, wheat and cotton, commonly grown crops in the region, of 1.7, 6.0 and 7.7 dSm1, respectively. However, soils with less water fluctuation showed lower salt accumulation in the root zone from May to October. Results also confirmed that soils can be non-saline, but groundwater salinity, which may not be point specific, requires special attention.